Positive electrode mixture
Patent Information
- Application Number
- JP2023081287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-05-17
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2043-05-17
AI Technical Summary
【0012】 本開示は、リチウム二次電池の放電容量を向上させることができる正極合材を提供することができる。
Smart Images

Figure 0007638323000005 
Figure 0007638323000001 
Figure 0007638323000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode mixture. [Background technology]
[0002] The development of lithium secondary batteries (also called lithium-sulfur batteries) using sulfur as the positive electrode active material is underway. Sulfur has the characteristic of having a very high theoretical capacity of 1675mAh / g.
[0003] Patent Document 1 discloses a positive electrode active material for lithium-sulfur batteries, which contains an amphiphilic polymer containing a hydrophilic portion and a hydrophobic portion, and a sulfur-carbon composite, as a technology for improving the electrical conductivity in the electrode, the cycle characteristics of the battery, and the capacity of the battery.
[0004] Patent Document 2 discloses a positive electrode material composed of a complex of sulfur and / or a sulfur compound having an S-S bond and a conductive material.
[0005] Patent Document 3 discloses a positive electrode including a current collector and a positive electrode active material layer containing a sulfur composite in which the surface of sulfur is covered with a metal layer or a metal sulfide layer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-506055 A [Patent Document 2] JP 2006-092881 A [Patent Document 3] JP 2014-035944 A Summary of the Invention [Problem to be solved by the invention]
[0007] Conventional lithium secondary batteries that use sulfur as a positive electrode active material have problems in that the proportion of materials other than the positive electrode active material in the positive electrode layer of the lithium secondary battery is high, the energy density of the positive electrode layer is low, and the discharge capacity of the lithium secondary battery is low.
[0008] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a positive electrode mixture that can improve the discharge capacity of a lithium secondary battery. [Means for solving the problem]
[0009] The present disclosure provides a positive electrode mixture for a lithium secondary battery, comprising: A positive electrode active material having an S element; Contains diphenyl disulfide as an additive, The positive electrode mixture has a content of the diphenyl disulfide of less than 13.0 mass % when the total mass of the positive electrode mixture is taken as 100 mass %.
[0010] In the positive electrode mixture of the present disclosure, the content of the diphenyl disulfide in the positive electrode mixture may be 0.8 mass % or more and 3.7 mass % or less, when the total mass of the positive electrode mixture is taken as 100 mass %.
[0011] The present disclosure provides a lithium secondary battery comprising: a positive electrode having a positive electrode layer containing the positive electrode mixture; a negative electrode having a negative electrode layer containing a negative electrode active material; and an electrolyte layer containing an electrolyte. Effect of the Invention
[0012] The present disclosure can provide a positive electrode mixture that can improve the discharge capacity of a lithium secondary battery. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional schematic diagram showing an example of a lithium secondary battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present disclosure provides a positive electrode mixture for a lithium secondary battery, comprising: A positive electrode active material having an S element; Contains diphenyl disulfide as an additive, The positive electrode mixture has a content of the diphenyl disulfide of less than 13.0 mass % when the total mass of the positive electrode mixture is taken as 100 mass %.
[0015] The present researchers discovered that by adding diphenyl disulfide, which has the characteristic of reacting with Li during charging, to a positive electrode mixture, the discharge capacity of a lithium secondary battery having a positive electrode layer containing the positive electrode mixture is significantly improved. Diphenyl disulfide, shown in the following chemical formula (1), is Li + It is known that diphenyl disulfide reacts with diphenyl disulfide, opens the ring, and produces a substance called lithium thiophenolate (LiTP) shown in the following chemical formula (2). Since LiTP has Li ion conductivity, it is believed that the ion conductivity in the positive electrode layer improves as Li reacts with diphenyl disulfide during charging of the lithium secondary battery. From the above, it is believed that the discharge capacity of the lithium secondary battery improves when diphenyl disulfide is included in the positive electrode layer.
[0016] [ka]
[0017] [ka]
[0018] The positive electrode mixture contains at least a positive electrode active material and diphenyl disulfide as an additive, and may contain a solid electrolyte, a conductive assistant, a binder, and the like, as necessary.
[0019] The positive electrode active material contains an S element. Various materials can be used as the positive electrode active material containing an S element. For example, the positive electrode active material can be elemental sulfur and Li X Examples of elemental sulfur include S8 sulfur. S8 sulfur can have three crystal forms, namely, α sulfur (orthorhombic sulfur), β sulfur (monoclinic sulfur), and γ sulfur (monoclinic sulfur), but any of these crystal forms may be used. The shape of the positive electrode active material is not particularly limited, and examples thereof include a particulate shape and a plate shape. When the positive electrode active material is in a particulate form, the average particle size of the positive electrode active material particles is not particularly limited. The positive electrode active material may contain a positive electrode active material other than the positive electrode active material containing an S element, as long as the above-mentioned problem can be solved.
[0020] The amount of the positive electrode active material contained in the positive electrode composite is not particularly limited, and may be appropriately determined according to the target battery performance. For example, the positive electrode composite may contain 10% by mass or more and 80% by mass or less of the positive electrode active material. The lower limit may be 15% by mass or more, 20% by mass or more, or 25% by mass or more. The upper limit may be 70% by mass or less, or 60% by mass or less. If the content of the positive electrode active material is too high, the ionic conductivity and electronic conductivity in the positive electrode layer of the lithium secondary battery may be insufficient.
[0021] As the additive, diphenyl disulfide is used. The amount of additive contained in the positive electrode mixture may be less than 13.0% by mass when the total mass of the positive electrode mixture is taken as 100% by mass, and from the viewpoint of further improving the discharge capacity of the lithium secondary battery, may be 0.8% by mass or more and 3.7% by mass or less. If the content of additive is too high, the content of the positive electrode active material becomes relatively small, and a positive electrode mixture having sufficient energy density may not be obtained.
[0022] The solid electrolyte has the function of improving the ionic conductivity of the positive electrode mixture. Examples of the solid electrolyte include the materials exemplified in the electrolyte layer described below. The content of the solid electrolyte in the positive electrode composite is not particularly limited, but may be, for example, 1% by mass to 80% by mass when the total mass of the positive electrode composite is taken as 100% by mass. If the content of the solid electrolyte is too high, the content of the positive electrode active material will be relatively low, and a positive electrode composite having sufficient energy density may not be obtained.
[0023] The conductive assistant has a function of improving the electronic conductivity of the positive electrode mixture. It is also assumed that the conductive assistant functions as a reducing agent that reduces elemental sulfur (positive electrode active material) when, for example, mechanical milling is performed on the raw material mixture. The conductive assistant may be present in a dispersed state in the positive electrode mixture. Examples of the conductive assistant include carbon materials and metal materials, etc. Examples of the carbon materials include vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), activated carbon, furnace black, carbon nanotubes (CNT), carbon nanofibers (CNF), and graphene, etc. The conductive assistant may be used alone or in combination of two or more kinds. The amount of the conductive assistant contained in the positive electrode composite is not particularly limited, and may be appropriately determined according to the intended battery performance. For example, the positive electrode composite may contain 5% by mass or more and 50% by mass or less of the conductive assistant. The lower limit may be 10% by mass or more. The upper limit may be 40% by mass or less. If the content of the conductive assistant is too high, the content of the positive electrode active material becomes relatively low, and a positive electrode composite having sufficient energy density may not be obtained.
[0024] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), and styrene butadiene rubber (SBR). The binder may be used alone or in combination of two or more kinds. The content of the binder in the positive electrode mixture is not particularly limited.
[0025] The positive electrode mixture may be in the form of a powder, a mass formed by agglomeration and / or bonding of a plurality of particles, or any other form. Various forms may be adopted depending on the intended form of the battery, etc.
[0026] The method for producing the positive electrode mixture in the present disclosure is not particularly limited, and the positive electrode mixture may be produced by mixing raw materials such as a positive electrode active material and additives. The means for mixing the raw materials is not particularly limited. For example, the raw materials may be mixed by mechanical milling. Mechanical milling is not particularly limited as long as it is a method of mixing raw materials while applying mechanical energy, and examples thereof include a ball mill, a vibration mill, a turbo mill, mechanofusion, and a disk mill. From the viewpoint of making it easier to make the raw materials amorphous, a planetary ball mill may be used.
[0027] The mechanical milling may be dry mechanical milling or wet mechanical milling. The liquid used in the wet mechanical milling may be, for example, aprotic liquid. Specifically, the liquid may be a polar aprotic liquid, a non-polar aprotic liquid, or the like.
[0028] The conditions of mechanical milling are appropriately set so as to obtain a desired positive electrode composite. For example, when using a planetary ball mill, the raw material mixture and grinding balls are added to a container, and processing is performed at a predetermined table rotation speed and time. The table rotation speed is, for example, 200 rpm or more, may be 300 rpm or more, or may be 500 rpm or more. On the other hand, the table rotation speed is, for example, 800 rpm or less, may be 600 rpm or less. In addition, the processing time of the planetary ball mill is, for example, 30 minutes or more, may be 5 hours or more. On the other hand, the processing time of the planetary ball mill is, for example, 100 hours or less, may be 60 hours or less. Examples of materials for the container and grinding balls used in the planetary ball mill include ZrO2 and Al2O3. The diameter of the grinding balls is, for example, 1 mm or more and 20 mm or less. It is preferable to perform mechanical milling in an inert gas atmosphere (for example, an Ar gas atmosphere).
[0029] 7. Lithium secondary batteries FIG. 1 is a cross-sectional view illustrating an example of a lithium secondary battery according to the present disclosure. As shown in FIG. 1, the lithium secondary battery 100 includes a positive electrode 16 including a positive electrode layer 12 and a positive electrode current collector 14, a negative electrode 17 including a negative electrode layer 13 and a negative electrode current collector 15, and an electrolyte layer 11 disposed between the positive electrode layer 12 and the negative electrode layer 13.
[0030] [Positive electrode] The positive electrode has at least a positive electrode layer, and if necessary, further includes a positive electrode current collector.
[0031] [Positive electrode layer] The positive electrode layer is made of the above-mentioned positive electrode mixture. The thickness of the positive electrode layer is not particularly limited, but may be, for example, 0.1 μm or more and 1000 μm or less.
[0032] The method for forming the positive electrode layer is not particularly limited, and for example, a powder of a positive electrode mixture containing a positive electrode active material, diphenyl disulfide, and other components as necessary is put into a solvent and stirred with a homogenizer or the like to prepare a slurry for the positive electrode layer, and the slurry for the positive electrode layer is applied onto one side of a support such as a positive electrode current collector and dried to obtain the positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, heptane, and N-methyl-2-pyrrolidone. The method for applying the positive electrode layer slurry onto one surface of a support such as a positive electrode current collector is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. As the support, a material having self-supporting properties can be appropriately selected and used, for example, a metal foil such as Cu or Al can be used.
[0033] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material, diphenyl disulfide, and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 600 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include methods of applying pressure using a flat press, a roll press, cold isostatic pressing (CIP), and the like.
[0034] [Positive electrode current collector] The positive electrode current collector has a function of collecting the current from the positive electrode layer. Examples of the material of the positive electrode current collector include metal materials containing at least one element selected from the group consisting of Ni, Al, Au, Pt, Fe, Ti, Co, and Cr. Note that, as long as the surface of the positive electrode current collector is made of the above material, the inside may be made of a material different from the surface. The positive electrode current collector may have various shapes, such as a foil shape, a plate shape, a mesh shape, and a punched metal shape. The positive electrode may further include a positive electrode lead connected to the positive electrode current collector.
[0035] [Negative electrode] The negative electrode includes a negative electrode layer and a negative electrode current collector that collects current from the negative electrode layer.
[0036] [Negative electrode layer] The negative electrode layer is a layer that contains at least a negative electrode active material. Examples of the negative electrode active material include lithium alone and lithium alloys. Examples of the lithium alloy include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. If the positive electrode layer contains a material containing Li, a Si alone or a Si alloy may be used as the negative electrode active material. Examples of the Si alloy include an alloy with a metal such as Li, and may also be an alloy with at least one metal selected from the group consisting of Sn, Ge, and Al. The negative electrode layer may contain at least one of a solid electrolyte, a conductive assistant, and a binder, as necessary. The solid electrolyte may be exemplified by the materials exemplified in the electrolyte layer described below. The conductive assistant and the binder may be exemplified by the materials exemplified in the positive electrode mixture described above. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 0.1 μm or more and 1000 μm or less. The negative electrode layer can be easily formed, for example, by pressing the above-mentioned negative electrode active material, etc. Alternatively, a foil made of the above-mentioned material may be used as the negative electrode layer.
[0037] [Negative electrode current collector] Examples of the material of the negative electrode current collector include metal materials such as SUS, Cu, Ni, Fe, Ti, Co, and Zn. Examples of the shape of the negative electrode current collector include the shapes exemplified for the positive electrode current collector described above.
[0038] [Electrolyte layer] The electrolyte layer includes at least an electrolyte. The electrolyte may be a non-aqueous electrolyte solution, a gel electrolyte, a solid electrolyte, etc. These may be used alone or in combination of two or more.
[0039] The non-aqueous electrolyte solution used generally contains a lithium salt and a non-aqueous solvent. Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2(Li-TFSI), LiN(SO2C2F5)2, and LiC(SO2CF3)3. Examples of non-aqueous solvents include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, sulfolane, acetonitrile (AcN), dimethoxymethane, 1,2-dimethoxyethane (DME), 1,3-dimethoxypropane, diethyl ether, tetraethylene glycol dimethyl ether (TEGDME), tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide (DMSO), and mixtures thereof. The concentration of the lithium salt in the non-aqueous electrolyte may be, for example, 0.3 to 5M.
[0040] A gel electrolyte is generally a gel formed by adding a polymer to a non-aqueous electrolyte solution. Specifically, the gel electrolyte can be obtained by adding a polymer such as polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyvinylidene fluoride (PVdF), polyurethane, polyacrylate, or cellulose to the nonaqueous electrolyte solution described above and gelling the solution.
[0041] Examples of the solid electrolyte (SE) contained in the electrolyte layer include sulfide-based solid electrolytes, oxide-based solid electrolytes, and polymer electrolytes, and among these, sulfide-based solid electrolytes are preferred. The sulfide-based solid electrolyte preferably contains Li, A (A is at least one of P, Ge, Si, Sn, B, and Al), and S. The sulfide-based solid electrolyte may further contain a halogen element. Examples of the halogen element include F, Cl, Br, and I, and F, Cl, and Br are preferred. The sulfide-based solid electrolyte may further contain O. Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2O5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, P2S5-Li3PO4-LiI, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any of P, Si, Ge, B, Al, Ga, and In.) The above description of "Li2S-P2S5" means a material obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. The molar ratio of each element in the sulfide-based solid electrolyte can be controlled by adjusting the content of each element in the raw material. The molar ratio and composition of each element in the sulfide-based solid electrolyte can be measured, for example, by ICP emission spectrometry.
[0042] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.
[0043] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.
[0044] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature is not particularly limited, and may be, for example, a temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis measurement, and is usually 195° C. or higher. On the other hand, the upper limit of the heat treatment temperature is not particularly limited. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.
[0045] The oxide-based solid electrolyte may be, for example, a substance having a garnet-type crystal structure containing Li, La, A (A is at least one of Zr, Nb, Ta, and Al), and O; 3+x PO4-x N x (1≦x≦3), etc.
[0046] The polymer electrolyte typically contains a lithium salt and a polymer. The lithium salt may be the above-mentioned inorganic lithium salt, organic lithium salt, etc. The polymer is not particularly limited as long as it forms a complex with the lithium salt, and examples thereof include polyethylene oxide, etc.
[0047] The shape of the solid electrolyte is not particularly limited, and examples thereof include a particulate shape and a plate shape. From the viewpoint of easy handling, the solid electrolyte may be in a particulate shape. Furthermore, the average particle size (D50) of the solid electrolyte particles is not particularly limited, but the lower limit may be 0.5 μm or more and the upper limit may be 2 μm or less.
[0048] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order of decreasing particle size.
[0049] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, and may be in the range of 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, or may be 100% by mass.
[0050] In the case where the electrolyte layer is a solid electrolyte layer, a binder may be contained from the viewpoint of expressing plasticity, etc. Examples of such binders include materials exemplified as binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.
[0051] The electrolyte layer may be impregnated with the above-mentioned non-aqueous electrolyte solution or the like, and a separator that prevents contact between the positive electrode layer and the negative electrode layer may be used. The material of the separator is not particularly limited as long as it is a porous film, and examples thereof include resins such as polyethylene (PE), polypropylene (PP), polyester, cellulose, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be a nonwoven fabric such as a resin nonwoven fabric or a glass fiber nonwoven fabric.
[0052] The thickness of the electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less.
[0053] The lithium secondary battery may optionally include an exterior body that contains a positive electrode, a negative electrode, and an electrolyte layer. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin.
[0054] The lithium secondary battery in the present disclosure may be a lithium-sulfur battery (LiS battery) that uses a material containing elemental sulfur as the positive electrode active material. Examples of the shape of the lithium secondary battery include a coin type, a laminate type, a cylindrical type, and a square type.
[0055] The method for producing the lithium secondary battery of the present disclosure is not particularly limited, and any conventionally known method can be used. In a method for producing a lithium secondary battery, for example, first, a solid electrolyte layer is formed by pressure molding a powder of a solid electrolyte material. Then, a powder of a positive electrode composite material containing a positive electrode active material and diphenyl disulfide is pressure molded on one side of the solid electrolyte layer to obtain a positive electrode layer. Then, a powder of a negative electrode composite material containing a negative electrode active material is pressure molded on the side of the solid electrolyte layer opposite to the side on which the positive electrode layer is formed to obtain a negative electrode layer. Then, a positive electrode current collector and a negative electrode current collector may be attached as necessary to form a lithium secondary battery. In this case, the pressing pressure when the powder of the solid electrolyte material, the powder of the positive electrode composite material, and the powder of the negative electrode composite material are press-molded is usually about 1 MPa or more and 600 MPa or less. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer. EXAMPLES
[0056] Example 1 (Preparation of positive electrode mixture) The raw materials prepared were elemental sulfur (positive electrode active material, manufactured by Kojundo Chemicals), Ketjen black (conductive assistant), and diphenyl disulfide (additive). Diphenyl disulfide was weighed out and used so as to be 0.8% by mass when the total mass of the resulting positive electrode mixture was taken as 100% by mass. These raw materials were mixed by melt quenching at 160°C for 10 hours to obtain a mixture. The mixture and the Li2S-P2S5-based sulfide-based solid electrolyte were then mechanically milled using a planetary ball mill (Fritsch P7) at a table rotation speed of 400 rpm for 6 hours. This resulted in a positive electrode composite. The mass ratio of each raw material is shown in Table 1.
[0057] (Production of lithium secondary batteries) 1cm 2100 mg of solid electrolyte was placed in a ceramic mold and pressed at a pressure of 30 bar (≒ 3 MPa) to obtain a solid electrolyte layer. On one side of the solid electrolyte layer, 4 mg of positive electrode composite material (weight: 4 mg / cm) was applied. 2 ) and pressed at a pressure of 30 bar (≒ 3 MPa) to create the positive electrode layer. A Li-In alloy foil, which serves as the negative electrode layer, was placed on the side of the solid electrolyte layer opposite the side on which the positive electrode layer was formed, to obtain a laminate having a positive electrode layer, solid electrolyte layer, and negative electrode layer in that order. The resulting laminate was restrained at a pressure of 2 N m to obtain a lithium secondary battery.
[0058] Example 2 A positive electrode mixture and a lithium secondary battery were obtained in the same manner as in Example 1, except that diphenyl disulfide was weighed out to be 3.7% by mass when the total mass of the resulting positive electrode mixture was taken as 100% by mass. The mass proportions of each raw material are shown in Table 1.
[0059] Comparative Example 1 Except for not using diphenyl disulfide, a positive electrode mixture and a lithium secondary battery were obtained in the same manner as in Example 1. The mass proportions of each raw material are shown in Table 1.
[0060] Comparative Example 2 A positive electrode mixture and a lithium secondary battery were obtained in the same manner as in Example 1, except that diphenyl disulfide was weighed out to be 13.0% by mass when the total mass of the resulting positive electrode mixture was 100% by mass. The mass proportions of each raw material are shown in Table 1.
[0061] Comparative Example 3 Except for using bis(2-nitrophenyl)disulfide represented by the following chemical formula (3) instead of diphenyldisulfide as an additive, a positive electrode mixture and a lithium secondary battery were obtained in the same manner as in Example 1. The mass proportions of each raw material are shown in Table 1.
[0062] [ka]
[0063] (Charge / discharge test) A charge-discharge test was performed on each of the lithium secondary batteries obtained in Examples 1-2 and Comparative Examples 1-3. In the charge-discharge test, the batteries were charged at a constant current (CC) of 0.5V to 2.5V at 60°C and 0.1C. The capacity per hour was calculated from the product of the time during which a constant current was applied and the current value when the batteries were discharged from 2.5V to 0.5V at 60°C and 0.1C, and the sum of the capacities was divided by the mass of sulfur to calculate the discharge capacity of each lithium secondary battery. In addition, the relative discharge capacity of each of the lithium secondary batteries in Examples 1-2 and Comparative Examples 2-3 was calculated with respect to the discharge capacity of the lithium secondary battery in Comparative Example 1, where the discharge capacity of the lithium secondary battery in Comparative Example 1 was taken as 100%. The results are shown in Table 1. In Table 1, the lithium secondary battery is simply referred to as a battery.
[0064] [Table 1]
[0065] From the results of Examples 1 and 2, it was confirmed that the inclusion of 0.8 to 3.7 mass % of diphenyl disulfide in the positive electrode mixture has the effect of improving the discharge capacity of a lithium secondary battery. On the other hand, from the results of Comparative Example 2, diphenyl disulfide and Li + Since the reaction with ZnO is not very fast, if the positive electrode mixture contains 13 mass % or more of ZnO, it is thought that this leads to an increase in the resistance of the positive electrode layer and a decrease in the discharge capacity of the lithium secondary battery. Initially, it was thought that the phenyl group of diphenyl disulfide was important for improving the discharge capacity of lithium secondary batteries. However, the results of Comparative Example 3 showed that when Bis(2-nitrophenyl)disulfide, which has a nitro group, was contained in the positive electrode mixture, the discharge capacity of the lithium secondary battery did not improve significantly. This is because Bis(2-nitrophenyl)disulfide is a + This is thought to be because it is difficult to produce a substance with Li-ion conductivity because it is difficult to react with Therefore, it was confirmed that diphenyl disulfide has a specific effect of improving the discharge capacity of a lithium secondary battery. From the above results, it was confirmed that the discharge capacity of a lithium secondary battery can be significantly improved by incorporating a small amount of diphenyl disulfide in the positive electrode mixture. [Explanation of symbols]
[0066] 11 Electrolyte layer 12 Positive electrode layer 13 Negative electrode layer 14 Positive electrode current collector 15 Negative electrode current collector 16 positive electrode 17 Negative electrode 100 Lithium secondary battery
Claims
1. A positive electrode mixture for a lithium secondary battery, comprising: A positive electrode active material having an S element; Contains diphenyl disulfide as an additive, A content of the diphenyl disulfide in the positive electrode mixture is 0.8% by mass or more and 3.7% by mass or less, when a total mass of the positive electrode mixture is 100% by mass.
2. 13. A lithium secondary battery comprising: a positive electrode having a positive electrode layer containing the positive electrode mixture according to claim 1; a negative electrode having a negative electrode layer containing a negative electrode active material; and an electrolyte layer containing an electrolyte.
Citation Information
Patent Citations
Sulfur-carbon / zinc-doped lithium iron phosphate composite positive electrode material and preparation method thereof
CN115148971A
Battery positive electrode material containing sulfur and / or sulfur compound having s-s bonding, and its manufacturing method
JP2006092881A
Positive electrode including sulfur composite and secondary battery
JP2014035944A
Coated lithium-nickel complex oxide particle and manufacturing method thereof
JP2016021323A
Positive electrode active material for lithium-sulfur battery and method for producing the same
JP2016506055A